2020
DOI: 10.1186/s13048-020-00737-1
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of the impact of COVID-19 on human reproductive biology, assisted reproduction care and pregnancy: a Canadian perspective

Abstract: Currently, the world is in the seventh month of the COVID-19 pandemic. Globally, infections with novel SARS-CoV-2 virus are continuously rising with mounting numbers of deaths. International and local public health responses, almost in synchrony, imposed restrictions to minimize spread of the virus, overload of health system capacity, and deficit of personal protective equipment (PPE). Although in most cases the symptoms are mild or absent, SARS-CoV-2 infection can lead to serious acute respiratory disease and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
126
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 129 publications
(164 reference statements)
1
126
0
10
Order By: Relevance
“…False positives could arise from contaminants or poor test specificity [41]. In any case, the sensitivity and specificity of the RT-PCR methods used to detect SARS-CoV-2 in seminal fluid have not been evaluated [42].…”
Section: Discussionmentioning
confidence: 99%
“…False positives could arise from contaminants or poor test specificity [41]. In any case, the sensitivity and specificity of the RT-PCR methods used to detect SARS-CoV-2 in seminal fluid have not been evaluated [42].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that viruses can cause inflammation of reproductive tissue; indeed, one of the most common clinical manifestations of mumps is orchitis, which can be damaging to testicular function. Furthermore, several case reports have discussed the development of orchitis in patients who have contracted COVID‐19 and small studies have shown pathological changes to testicular tissue 2 . A possible mechanism for this is expressed in Figure 1.…”
Section: Figurementioning
confidence: 99%
“…While the data regarding whether SARS-CoV-2 is present in semen of infected or recovering men remains conflicting, most of the studies suggest that it is highly unlikely that the virus is sexually transmitted. 160 Indeed, three studies that examined the sexual transmission of COVID-19 in women by examining lower genital tract via vaginal swab for the presence of SARS-CoV-2 at the time of admission or during the period of hospitalization have reported negative results. [161][162][163] Similar results were reported with vaginal swabs and breast milk from pregnant women.…”
Section: Pathology In Renal Hepatic Reproductive and Neural Tissuesmentioning
confidence: 99%